Culture's influence regionally differing social milieus and variations in fertility rates - Barbara Fulda (Max Planck Institute for the Study of Societies, 2015)
How can we understand subnational differences in fertility rates? The most common explanations see the key to these differences in the socio-structural composition of a region's population and its structural conditions. However, such explanations fail to account for fertility rate differences in regions with similar populations and structures. This paper analyzes two social milieus in southern Germany and argues that variations in their fertility rates can only be understood through their cultural differences. Family extension patterns as well as opportunity structures (such as the availability of childcare facilities) are substantially influenced by the regionally differing cultural norms formed and held by social milieu members. To better explain differences in fertility rates and to understand the regionally differing effects of family policy measures, demographic research therefore needs to include culture in its understanding of demographic behavior. – – Warum unterscheiden sich regionale Geburtenraten in Deutschland? Die Forschung begründet die großen Unterschiede mit der soziostrukturellen Zusammensetzung der Bevölkerung und den strukturellen Bedingungen einer Region. Unterschiede der Fertilitätsraten zwischen Regionen, deren Bevölkerung und Struktur sich ähneln, können hierdurch jedoch nicht erklärt werden. Die Analyse zweier sozialer Milieus in Süddeutschland zeigt, dass kulturelle Unterschiede ein weiterer wichtiger Erklärungsfaktor sind. Erstens werden strukturelle Gegebenheiten (zum Beispiel Angebote der Kinderbetreuung und das Vereinsleben) durch die Angehörigen eines sozialen Milieus als Träger regionaler sozialer Normen ausgestaltet, was Auswirkungen auf die Lebensbedingungen von Familien hat. Zweitens werden Milieumitglieder durch diese kulturelle Normen in ihrem Familienerweiterungsverhalten beeinflusst. Um regional unterschiedliche Auswirkungen familienpolitischer Maßnahmen auf Fertilitätsraten zu verstehen, sollte zukünftige demografische Forschung kulturelle Unterschiede berücksichtigen.
Keywords: 300